Thermal Processing of Food Products by Steam and Hot Water Unit Operations and Processing Equipment in the Food Industry - Jafari, Seid Mahdi; Jafari, Seid Mahdi (Woodhead Publishing, 2022)
Thermal Processing of Food Products by Steam and Hot Water, a volume in the Unit Operations and Processing Equipment in the Food Industry series, explains the processing operations and equipment necessary for the thermal processing of different food products by applying steam and hot water. Sections cover an overview of thermal food processing, heat exchangers in the food processing industry, different thermal processing operations in the food industry, and applications of heat exchanges. All sections emphasize basic texts relating to experimental, theoretical, computational and/or the applications of food engineering principles and relevant processing equipment. Written by experts in the field of food engineering, in a simple and dynamic way, this book targets industrial engineers working in the field of food processing and within food factories to make them more familiar with the particular food processing operations and equipment. - Thoroughly explores novel applications of thermal unit operations in the food industry - Evaluates different alternatives for thermal processing operations - Covers the application of heat exchangers in the food industry